Integrasi Kurikulum Literasi Digital pada Sekolah Alam: Generasi Alpha Tanggap Cyberbulliying dalam Penggunaan Teknologi - Rahima Nurviani; Nurasiah Nurasiah; Luh Ayu Auranisa; Rahmy Zulmaulida (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
Digital gadgets are now common in elementary schools, offering many benefits for learning. However, they also bring new problems, with cyberbullying being a serious risk for young children. This project aimed to teach students at Sekolah Alam Bireuen about cyberbullying—what it is, how it hurts people, and how to stop it. We worked with 20 students in grades 5 and 6. Using hands-on activities like discussions and role-playing, we helped them understand the different roles in a cyberbullying situation: the target, the person doing the bullying, and the witnesses. The students showed a strong increase in their understanding and pledged to be "Digital Heroes" who use technology kindly and responsibly. This work shows that directly teaching children about online safety is a necessary and effective part of modern education.